2013
DOI: 10.4103/0976-237x.123069
|View full text |Cite
|
Sign up to set email alerts
|

Retrieval of a metallic obstruction from the root canal of a premolar using Masserann technique

Abstract: A metallic obstruction in the root canal blocks canal cleaning and shaping procedures and requires either bypassing or retrieval. Many methods have been recommended to retrieve a metallic obstruction from the root canal. This article describes the retrieval of a metallic obstruction from the root canal of a premolar using Masserann technique to facilitate endodontic retreatment. Masserann technique is said to have limited application in posteriors. However, in this case, the obstruction was successfully retrie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…Furthermore, numerous studies prove that root canal fillings containing broken endodontic instruments have no effect on the long-term prognosis. (Crump et al) [17] Saunder's study on bacterial penetration of filled root canals also showed that there was no significant difference between the group of sealed canals containing separated files and those without broken files [18].…”
Section: Resultsmentioning
confidence: 97%
“…Furthermore, numerous studies prove that root canal fillings containing broken endodontic instruments have no effect on the long-term prognosis. (Crump et al) [17] Saunder's study on bacterial penetration of filled root canals also showed that there was no significant difference between the group of sealed canals containing separated files and those without broken files [18].…”
Section: Resultsmentioning
confidence: 97%
“…Surgical and nonsurgical approaches are available ways for dealing with the tooth with fractured instruments. Nonsurgical approaches include the retrieval of the instrument and its bypass or obturating up to the level of the instrument [ 11 ]. The ability to securely remove a fractured fragment is further constrained by the complex anatomy of the canal, which includes root dentin thickness and its curvature.…”
Section: Discussionmentioning
confidence: 99%
“…These anatomical differences in the canal put patients at risk of a range of iatrogenic issues, including missing canals, instrument separation, gouging, perforation, and excessive extension of the obturation materials. One such unfavorable occurrence is instrument breakage, which may impede the cleaning and shaping processes and cause pain or discomfort [ 1 ]. Instrument separation is one of the most common reasons for the failure of root canal treatments.…”
Section: Introductionmentioning
confidence: 99%